Advances in smart vehicular technology, transportation, communication and applications : proceedings of the First International Conference on Smart Vehicular Technology, Transportation, Communication and Applications, November 6-8, 2017, Kaohsiung, Taiwan /: proceedings of the First International Conference on Smart Vehicular Technology, Transportation, Communication and Applications, November 6-8, 2017, Kaohsiung, Taiwan. (2017) - Unknown
No abstract available